2018
DOI: 10.1111/jnc.14292
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Palmitate‐induced C/EBP homologous protein activation leads to NF‐κB‐mediated increase in BACE1 activity and amyloid beta genesis

Abstract: The etiology of Alzheimer's disease (AD) is egregiously comprehended, but epidemiological studies have posited that diets rich in the saturated fatty acid palmitic acid (palmitate) are a significant risk factor. The production and accumulation of amyloid beta peptide (Aβ) is considered the core pathological molecular event in the pathogenesis of AD. The rate-limiting step in Aβ genesis from amyloid-β precursor protein (AβPP) is catalyzed by the enzyme β-site amyloid precursor protein cleaving enzyme 1 (BACE1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 109 publications
(246 reference statements)
1
16
0
Order By: Relevance
“…The effects of palmitateenriched diets and exogenous palmitate on the regulatory mechanisms involved in BACE1 expression and Aβ genesis have also not been exhaustively elucidated, with very few studies having determined the role of palmitate per se, and not high saturated fat diet, in the regulation of BACE1 expression and Aβ genesis. Our previous study has demonstrated that a palmitate-enriched diet, as well as treatment of cultured cells with exogenous palmitate, increases phosphorylation of tau, enhances BACE1 expression and the subsequent Aβ genesis, by evoking endoplasmic reticulum (ER) stress and C/EBP Homologous Protein (CHOP) activation [21,22,33]. Other studies have shown the effects of exogenous palmitate on BACE1 expression in primary cortical neuronal cultures and primary astrocytic cultures in vitro [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of palmitateenriched diets and exogenous palmitate on the regulatory mechanisms involved in BACE1 expression and Aβ genesis have also not been exhaustively elucidated, with very few studies having determined the role of palmitate per se, and not high saturated fat diet, in the regulation of BACE1 expression and Aβ genesis. Our previous study has demonstrated that a palmitate-enriched diet, as well as treatment of cultured cells with exogenous palmitate, increases phosphorylation of tau, enhances BACE1 expression and the subsequent Aβ genesis, by evoking endoplasmic reticulum (ER) stress and C/EBP Homologous Protein (CHOP) activation [21,22,33]. Other studies have shown the effects of exogenous palmitate on BACE1 expression in primary cortical neuronal cultures and primary astrocytic cultures in vitro [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…N2a-APP Swe/In cells were transfected with the designated vectors as previously described [24]. Transfected N2a-APP Swe/In cells were treated with BSA (bovine serum albumin)conjugated palmitate as shown previously [21,22]. Briefly, palmitate stock solution of 250mM was prepared in 100% ethanol.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations